On the issue of non-fiction literature in the Belarusian scientific discourse - Gubskaya, Olga N. (Journal of the Belarusian State University. Journalism, 2022)
This article is devoted to the study of the cause of occurrence of the concept of «non-fiction literature» (an alternative term is «new journalism»), the definition of the historical and cultural context that became the trigger for the formation of a whole phenomenon in literature and journalism. It is emphasised that the «non-fiction novel» is an American literary phenomenon that was formed as a reaction to the cultural and political situation in the USA in the 1960s. If in American literature and journalism it was first recorded and then analysed,then in the Belarusian scientific discourse the phenomenon began to be coordinated with the ready-made term, which led to its fairly wide use. As a result, it is concluded that there are two general concepts that clearly reflect the essence of the American literary direction of non-fiction and can be applied in the consideration of Belarusian literature – this is the concept of «hybrid form of literature» and «the literature of fact». The opinion is also expressed that all the prerequisites have been created in modern Belarusian literature for literary studies to make a clear distinction between such concepts as literature of fact and ego-document.